Filosofia del linguaggio e critica alla linguistica nei primi scritti di Giorgio Agamben - D'Alonzo, Jacopo (Rivista Italiana di Filosofia del Linguaggio, 2015)
As philosopher, Giorgio Agamben is known for his political writings. However the problem of language is an important issue also in his most recent essays. Considering a time span ranging from the late sixties until the early nineties, this article tries handing in Agamben’s linguistic reflections. On the one hand, Agamben’s linguistic reflection represent an essential starting point to fully understand his political proposal. On the other hand, Agamben can be considered without doubt a philosopher of language. Additionally, this article does not exclude an analysis of both the characteristics and the unsuitableness of his philosophy of language. Finally, with regard to this suggestions, it seems to be important the reference to the more general historical, philosophical and linguistic context of the period when the early work of Agamben have been published.